Improved anticipatory scheduling algorithm based on workload characteristic and service time evaluation - Jin-zhong CHEN; Nian-min YAO; Shao-bin CAI; Mei-ling SUN (Tongxin xuebao)
Anticipatory scheduling (AS) of Linux I/O schedule layer assigns fixed anticipation period length to each process.It will introduce extra delay if I/O request does not arrive in time.The improved anticipatory scheduling (WPCAS) algorithm is proposed which is based on workload characteristic and service time.WPCAS includes process classifier(PC) module and request service time evaluation (STE) module.PC module assigns different anticipation period lengths in terms of workload characteristic.STE module decides whether to anticipate the coming request according to service time.Experimental results show that WPCAS algorithm is superior to 95%-Heuristic and AS in terms of throughput,average waiting time of anticipation success and deceptive idleness.